2001
DOI: 10.4039/ent133729-5
|View full text |Cite
|
Sign up to set email alerts
|

Control of conifer defoliators with neem-based systemic bioinsecticides using a novel injection device

Abstract: A systemic tree injection tube was designed to introduce the required volumes of neem-based bioinsecticides into conifer trees. The device consists of plastic tubing attached with hose clamps to a maple sap spile at one end and a tubeless automobile tire valve at the other end. A hole is drilled in the tree, the spile is hammered into the hole, the device is filled with the systemic insecticide, and the system is pressurized by attaching a bicycle pump to the tire valve. The parts are readily available, the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…The water-dissolved substance was injected into the tree at a concentration of 1:20 (g substance to ml water) for 10 hours. This was done using a tree injector according to Helson et al (2001). The 'injection' consisted of a maple sap spile, a piece of plastic tubing cut to the length needed to accommodate the required volume of insecticide, a tubeless automobile tire stem with a valve, and two hose clamps.…”
Section: Methodsmentioning
confidence: 99%
“…The water-dissolved substance was injected into the tree at a concentration of 1:20 (g substance to ml water) for 10 hours. This was done using a tree injector according to Helson et al (2001). The 'injection' consisted of a maple sap spile, a piece of plastic tubing cut to the length needed to accommodate the required volume of insecticide, a tubeless automobile tire stem with a valve, and two hose clamps.…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been shown that the systemic eVect of azadirachtin on herbivores can last much longer. Helson et al (2001) applied injection of azadirachtin (0.1 g active ingredient/cm trunk diameter) to white pine (Pinus strobus) and achieved mortality rates of the pine sawXy Diprion similes of 83-100%, sustained over a period of 77 days. Altogether, these results show that the duration of eVects of systemic tree injection of azadirachtin varies within a wide range.…”
Section: Discussionmentioning
confidence: 99%
“…The water-dissolved substance was injected into the tree at a concentration of 1:40 (g substance to ml water) for 10 h. This was done using a tree injector after Helson et al (2001), which was modiWed according to product application recommendation (one drill hole per meter crown diameter) of Trifolio-M for the use in litchi trees. The components of the tree injector ( Fig.…”
Section: Tree Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of extracts of the Neem tree have been developed 25 and used both historically, and up until present day, for an equally wide variety of benefits including crop protection, veterinary and human health 2, 3 . More recently, azadirachtins have been developed as natural, systemic insecticides for use in integrated pest management strategies against exotic invasive 30 wood-boring insect pests such as Emerald Ash Borer [4][5][6][7] . Formulated products based on Neem seed extracts contain high levels of different azadirachtin analogues, being the major forms Azadirachtin A and B 8 .…”
Section: Introductionmentioning
confidence: 99%